Effects of fabrication conditions on the microstucture and performance PES membrane: article - Nik Mohamed Kamal, Nik Shamimi Nazma; Othman, Nurhidayati (2017)
Phase inversion is a flexible technique that can be used to prepare membrane with various microstructure / morphologies targeted for fluid separation. Effects of membrane preparation parameter towards the morphology of polyethersufone (PES) membrane was investigated by varying the polymer compositions from 15 wt% to 25 wt% where Dimethyl acetamide (DMAc) was used as a solvent while polyvinylpyrrolidone (PVP) was used as a pore forming additive during the membrane preparation.